Is in vivo sensing in a total hip replacement a possibility? A review on past systems and future challenges. (16th September 2021) - Vickers, O G; Culmer, P R; Isaac, G H; Kay, R W; Shuttleworth, M P; Board, T; Williams, S
Abstract: Surgery to implant a total hip replacement (THR) is very successful in reducing pain and restoring function. This procedure has become more prevalent, and projections estimate further increases in demand. However, complications can arise, and current diagnostic techniques often fail to expose underlying issues before they result in a catastrophic failure that requires revision surgery. An instrumented implant, with embedded sensors capable of real time condition monitoring, would be an attractive proposition to incorporate within a THR. Continued advances in the performance and miniaturisation of electronic components, embedded systems, sensing and wireless communications have given the tools and resources medical device manufacturers need to innovate in the field of implantable medical devices. Smart implants are already being widely used in healthcare including pacemakers, cochlear implants, glucose monitors and insulin pumps however, a widely used smart THR has not yet been realised. Since the implantation of the first instrumented hip implant in the 1960s there have been several in vitro studies monitoring levels of implant loosening. Additionally, significant research has been conducted using instrumented THRs to perform in vivo measurement of biomechanical metrics, including force and moments. To date less than 100 patients have successfully received an instrumented implant. The results of these studies have aided researchers, designers and surgeons in wider research projects, however, the motivation behind the work was to provide discrete biomechanical data sets and not provide real-time condition monitoring of an implants performance or highlight early indications for revision surgery. If in vivo sensing within a THR is to be achieved and adopted in regular clinical practice then the following challenges need to be addressed: choice of the sensing method, biocompatibility and integration within the implant, power supply, communication, and regulatory considerations.